(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research seeks to understand the essence and implementation of collaborative leadership in efforts to enhance educational quality through stakeholder synergy at SD Lukman Al Hakim in Batu Kajang, East Kalimantan. Adopting a qualitative phenomenological method, the study investigates the lived experiences of key educational stakeholders including the school principal, teachers, parents, and the school committee using in-depth interviews, participant observation, and document analysis. The results indicate that collaborative leadership fosters a participatory culture and transparent communication, while also reinforcing shared responsibility in both decision-making and program implementation. This collaborative approach builds synergistic, adaptive, and improvement-driven relationships that contribute to the advancement of educational service quality. Moreover, the study highlights collaborative leadership as a vital approach to overcoming educational challenges in remote regions by empowering the school community and cultivating an inclusive, student-centered learning environment.